Neonatal testosterone exposure alleviates female-specific severity of formalin-induced inflammatory pain in mice - Moeko Kanaya; Moeko Kanaya; Yoshifumi Ueta; Makiko Mochizuki-Kashio; Ayako Nakamura-Ishizu; Mariko Miyata (Frontiers in Neural Circuits, 2025)
Gonadal hormones may influence higher pain sensitivity in females than males by transiently activating the central pain pathway and organizing sexually dimorphic neuronal circuits during development. The latter effects of gonadal hormones, called organizational effects, are critical for establishing sex-specific reproductive functions and transforming them postnatally. However, it remains unclear whether the organizational effects determine sex-specific pain severity in adulthood. In this study, testosterone administration to female mice on day of birth alleviated intraplantar formalin injection-induced inflammatory pain in adulthood, resulting in comparable severity to males. In contrast, intense pain persisted in females with adult testosterone administration. We found no sex differences in thermal pain responses and spinal reflexes. Formalin injection similarly increased c-Fos activity in the spinal dorsal horn in both sexes, suggesting the involvement of supraspinal mechanisms and/or immune responses in sex-specific inflammatory pain. In the periaqueductal gray (PAG) region related to the descending pain modulation pathway, formalin increased c-Fos-positive cells in the lateral region of males but not females. In the bed nucleus of the stria terminalis (BNST) related to affective pain responses, formalin increased c-Fos-positive cells in females. Notably, in common with these regions, testosterone administration to neonatal females changed formalin-induced c-Fos activity from the female to the male type. We further examined the involvement of immune cells. Systemic microglial ablation using PLX3397 suppressed formalin-induced pain in a sex-independent manner. Although formalin injection changed T lymphocyte subsets in the peripheral blood in females, it was independent from neonatal testosterone administration. Therefore, the organizational effects of testosterone determine the male characteristic of formalin-induced inflammatory pain, possibly via sexually dimorphic PAG and BNST functions.